On vulnerability: a critical introduction - Brown, Patrick (Routledge, 2022)
"On Vulnerability maps out an array of perspectives for critically examining the nature of vulnerability, its unequal patterning across different social groups, alongside the everyday social processes which make us vulnerable - interactions, identity and group dynamics. Each chapter equips the reader with a particular sensitising framework for navigating and questioning what it means to be vulnerable or how people cope amid vulnerability. From deviance, stigma and the spoiling or fracturing of identity, to perspectives such as intersectionality, risk, emotions and the vulnerable body, the book traces the theoretical roots of these different analytical lenses, before applying these through illuminating examples and case studies. Drawing on scholarship across more interpretative, analytic and critical traditions, the chapters combine into a multidimensional toolkit which will enable the study of cultural meanings of vulnerability, the political-economic factors that shape its patterning, with a critical sensibility for 'unlearning' the many assumptions, challenging our sense of who is, or who can be, vulnerable. This book is designed to equip undergraduate and post-graduate students and researchers across the social, health and human sciences, aiding them as they study and question the experiences and structures of vulnerability in our social world"--